Adoption of Digital Innovations: A Special Referenceto Routinised Incremental Innovations. (December 2021) - Dutta, Dorothy; Sarma, Mrinmoy K.
The study's main purpose is to determine the adoption of digital innovations in a developing country that is continuously introduced on different service platforms. A quantitative approach is taken in the research where structured questionnaires based on the unified theory of acceptance and use of technology (UTAUT) model have been used to collect primary data. A total of 821 responses were selected for analysis using structural equation modelling. The findings suggest that the UTAUT model indicates a good fit for determining the behavioural intention to adopt incremental innovations in digital platforms. The model as a whole explains 31.6% of the total variance in the behavioural intention to adopt. Out of the four variables in the UTAUT model, social influence (SI) is seen to have no significant relationship with that of behavioural intention. However, the other three factors, namely performance expectancy (PE), effort expectancy (EE) and facilitating conditions (FC), do have a significant impact on the behavioural intention to adopt incremental innovations. FC has the greatest influence on the behavioural intention, followed by PE and EE. But important factors like age, gender, internet experience and voluntariness to use that are considered moderators are not seen to impact this aspect. Research focussing on radical innovations is quite abundant in past literature; however, those focusing on incremental innovations are quite scarce. This research, focussing on the adoption of incremental innovation in digital platforms in a developing country with a digital divide situation, is indeed a novel attempt. JEL Classification: O1, O2, O320